Academic Buoyancy and Peer Support as Predictors of Student Engagement in Learners within Compulsory Education - Fadila, Devia Rahma Hamimatul; Fathiyah, Kartika Nur (Journal of Basic Education Research, 2025)
Purpose of the study: This study aims to examine academic buoyancy and peer support as predictors of student engagement in high school students Methodology: This study is a quantitative study involving 324 high school students in Madiun who were selected by random sampling. The research instrument in this study used three scales: the student engagement scale, the academic buoyancy scale, and the peer support scale. Validity testing used content validity using the Gregory formula, while reliability using Chronbach Alpha with a value of 0.863 for the student engagement scale, 0.629 for the academic buoyancy scale, and 0.865 for the peer support scale. The data were analyzed using multiple linear regression techniques. Main Findings: The results of the study showed that academic buoyancy and peer support simultaneously had a significant influence on student engagement, which means that academic buoyancy and peer support together were predictors of student engagement in high school students Novelty/Originality of this study: This study reveals the unique role of academic buoyancy and peer support as predictors of high school student engagement, presenting a new perspective that combines academic resilience and social relationships in predicting learning engagement holistically.